2019
DOI: 10.3390/su11113203
|View full text |Cite
|
Sign up to set email alerts
|

ICT and the Sustainability of World Heritage Sites. Analysis of Senior Citizens’ Use of Tourism Apps

Abstract: Information and Communication Technologies (ICT) and applications (apps) for tourists are key tools for the sustainability of World Cultural Heritage Sites (WCHS). Their integration into tourism marketing strategies poses challenges regarding the satisfaction of the expectations of the target stakeholders, particularly senior tourists, people aged 60 and over. This paper adopts an exploratory and descriptive approach that combines qualitative techniques (focus groups), to study the use senior citizens make of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
1
29
0
2
Order By: Relevance
“…Effectively, within the wide range of ICTs, smartphones have revolutionized the way tourists interact with the physical and digital worlds, and have become essential and highly valued tools [36,49,50] thanks to their capacity to shape and enhance the tourist experience [36,42,51,52], which in turn can favor the promotion and dissemination of the destination by tourists themselves through word of mouth (WOM) and electronic word of mouth (eWOM) [53][54][55][56][57][58][59].…”
Section: Smartphones At the Service Of The Tourist Experiencementioning
confidence: 99%
See 3 more Smart Citations
“…Effectively, within the wide range of ICTs, smartphones have revolutionized the way tourists interact with the physical and digital worlds, and have become essential and highly valued tools [36,49,50] thanks to their capacity to shape and enhance the tourist experience [36,42,51,52], which in turn can favor the promotion and dissemination of the destination by tourists themselves through word of mouth (WOM) and electronic word of mouth (eWOM) [53][54][55][56][57][58][59].…”
Section: Smartphones At the Service Of The Tourist Experiencementioning
confidence: 99%
“…Hence the need is to identify the main uses given to smartphones for tourist purposes according to different generations and the consequent ICTs use habits [36], which is one of the objectives of this study. This information is necessary to successfully integrate smartphones into the digital marketing and communication strategies of tourist destinations.…”
Section: Smartphones At the Service Of The Tourist Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…This does not only concern the young and middle age, technology-oriented tourists. As a recent study from Spain [78] has shown, the line of age in which tourists use apps has shifted, and senior citizens are a substantial tourist group that uses ICT technologies, mainly in the pre-travel phase, to book accommodation and transportation, and to locate and search for services and products.…”
mentioning
confidence: 99%